PTU-186 The "speedboat-rs2": A New Multi-modality Endoscopic Device For Gastric And Oesophageal Submucosal Dissection And Tunnelling. (9th June 2014) - Tsiamoulos, ZP; Hancock, C; Sibbons, PD; Bourikas, LA; Saunders, BP
Abstract : Introduction: Gastric and oesophageal mucosal lesions are optimally removed en-bloc for accurate histology and complete resection. We describe, a simple to use, multi-modality endoscopic device ("Speedboat-RS2") for en-bloc gastric/oesophageal mucosal resection and for oesophageal submucosal tunnelling. Methods: The 'Speedboat-RS2' cuts in forward, lateral and oblique planes using bipolar radio frequency (RF) cutting, provides haemostasis with microwave coagulation and incorporates a retractable needle for submucosal injection and tissue irrigation. The instrument blade has an insulated 'hull' to prevent thermal injury to the muscularis propria and the device catheter is partially torque stable allowing rotation and orientation of the hull parallel to the muscle layer. Gastric submucosal dissection and oesophageal submucosal resections/tunnelling procedures were performed on 5 consecutive 60kg pigs. All cases were video recorded. The time taken to complete resection/tunnelling, complications encountered and power settings used were recorded. Two animals were euthanized immediately (termination study – TS) and three animals were recovered for 3 days (survival study = SS). Submucosal defects and excised flaps were measured and assessed histologically. Results: Five (3TS, 2SS) consecutive gastric submucosal dissections, 5 oesophageal resections 4 (3TS, 1SS) semi and 1 (SS) full circumferential oesophageal mucosal resections and 2 submucosal tunnelling procedures 1 (SS) with partial myotomy and 1 (TS) with no myotomy were performed. The median time to complete a gastric resection was 46 min range (21–83min) using RF cutting 35 W and 41 min range (12–50 min) using RF cutting 25W for the oesophageal excision/tunnelling procedure. Median gastric defect size was 55 mm, range 35–70 mm and median oesophageal defect size was 47 mm, range 35–70 mm. Microwave coagulation was applied for either minor bleeding or visible vessels on 57 occasions (mean energy 7.5 W). No endoscopic or histologic perforations were noted. All excised flaps were appropriate for histological assessment apart from one oesophageal flap that was mildly heat damaged. Gastric and oesophageal muscle layers/serosa were intact and viable. In three oesophageal cases, there was a mild muscle cell alteration but contiguity was retained. In one gastric resection, another dissection knife assisted the last ribbon cut. Conclusion: This initial evaluation of "Speedboat-RS2" in the upper GI tract suggests that it facilitates rapid and safe en-bloc mucosal resection in the oesophagus and stomach. It also appears promising for safe and rapid submucosal tunnelling in the oesophagus and has potential to be utilised for POEM. Disclosure of Interest: Z. Tsiamoulos Consultant for: Creo Medical Ltd, C. Hancock Shareholder of: Creo Medical Ltd, P. Sibbons Paid instructor for: Creo Medical Ltd, L. Bourikas: None Declared, B. Saunders: None Declared.